Molecular Bases of Pseudo-homozygous APC Resistance: The Compound Heterozygosity for FV R506Q and a FV Null Mutation Results in the Exclusive Presence of FV Leiden Molecules in Plasma - Castoldi, Elisabetta; Kalafatis, Michael; Lunghi, Barbara; Simioni, Paolo; Ioannou, Panayiotis A.; Petio, Margherita; Girolami, Antonio; Mann, Kenneth G.; Bernardi, Francesco (Thrombosis and Haemostasis, 1998)
Pseudo-homozygous APC resistance, the condition resulting from compound heterozygosity for FV R506Q (FV Leiden) and quantitative FV deficiency, provides a natural model to study the interaction between procoagulant and anticoagulant defects. This paper reports a complete FV characterization of a pseudo-homozygous APC resistant thrombotic patient. The expression of the patient’s non-Leiden gene was found to be severely impaired both at the mRNA and protein levels. In particular, only FV Leiden molecules were detected in the patient’s plasma by immunoblotting, which accounts for the observed marked APC resistance. Analysis of the FV cDNA obtained by reverse transcription of platelet RNA revealed that the mRNA of the non-Leiden gene was extremely reduced in amount. A PAC clone containing the whole FV gene was used to design primers for a complete FV exon scanning. A 2-bp insertion at nucleotide 3706 in the large exon 13 of the non-Leiden gene, predicting a frame-shift and premature termination of protein synthesis, was identified as responsible for the FV defect. Failure to find any case of pseudo-homozygous APC resistance in a large sample (6,804) of blood donors suggests that this condition is extremely rare among normal controls and that its detection is favoured by the thrombotic risk that it may confer.